Reinventing the Paradigm of Teaching: Implication for Teacher Education - Khirwadkar, Anjali (JOURNAL OF INDIAN EDUCATION, 2007)
At every stage and development of education, quality has always been a great concern. The great Indian thinkers emphasised on developing inner potentials of individuals. The NCF-2005 states that the curriculum must enable students to find their voices, nurture their curiosity to do things, to ask questions and to pursue investigations, sharing and integrating their experiences with school knowledge rather than their ability to produce textual knowledge. ICT provides to play an active role to the students necessary for quality learning. The web-based teaching-learning practice is the art, craft and science of using network technologies. It provides to the students a wide range of scopes for integrating varied learning experiences and making learning a holistic one.